Democracy as a Goal of Union Organization : An Interpretation of the United States Experience - Muthuchidambaram, S. (Relations industrielles / Industrial Relations, 1969)
This paper presents a overall review and an interpretation of the vast existing literature on union democracy in the United States.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z